2007
DOI: 10.1093/eurpub/ckm005
|View full text |Cite
|
Sign up to set email alerts
|

Statins prescribing for the secondary prevention of ischaemic heart disease in Torino, Italy. A case of ageism and social inequalities

Abstract: The prevention of IHD with statins is influenced by age, clinical and social factors. The prescribing rate is higher among population groups for whom statins are of proven efficacy. Among patients for whom the efficacy is uncertain, the decision to prescribe is influenced by non-clinical factors, suggesting that there exist both age-based and social-based mechanisms of rationing. Age and social determinants act in concert to further reduce the propensity of physicians to prescribe statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
24
2
Order By: Relevance
“…This is interesting and does not suggest that GP prescribing practice is solely based on calculated 10-year CVD risk. Contrary to previous reports, [39][40][41][42] however, the study found little difference in secondary prevention associated with age or sex, except in patients with heart failure and peripheral vascular disease, where a higher number of older patients and males were receiving therapy. This may reflect the 74-year age cut-off in this study.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 99%
“…This is interesting and does not suggest that GP prescribing practice is solely based on calculated 10-year CVD risk. Contrary to previous reports, [39][40][41][42] however, the study found little difference in secondary prevention associated with age or sex, except in patients with heart failure and peripheral vascular disease, where a higher number of older patients and males were receiving therapy. This may reflect the 74-year age cut-off in this study.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 99%
“…Patients over the age of 80 were less likely to receive statins for secondary prevention compared with other age groups. This has also been found in other studies [20,21]. In the national guidelines, there is no upper age limit for patients to be prescribed statins after stroke.…”
Section: Discussionsupporting
confidence: 82%
“…(7,8) Previous research has shown a 'treatment-risk' paradox for secondary prevention, whereby patients become less likely to receive appropriate treatment as they advance in age. (9,10) Compared to men, women have been found to be less frequently prescribed both antihypertensive and lipid-lowering drugs. (8,11) Up to 5% of all hospital admissions are the result of adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 99%